2014
DOI: 10.1038/mt.2014.113
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-103-1 Selectively Downregulates Brain NCX1 and Its Inhibition by Anti-miRNA Ameliorates Stroke Damage and Neurological Deficits

Abstract: Na(+)/Ca2+ exchanger (NCX) is a plasma membrane transporter that, by regulating Ca2+ and Na(+) homeostasis, contributes to brain stroke damage. The objectives of this study were to investigate whether there might be miRNAs in the brain able to regulate NCX1 expression and, thereafter, to set up a valid therapeutic strategy able to reduce stroke-induced brain damage by regulating NCX1 expression. Thus, we tested whether miR-103-1, a microRNA belonging to the miR-103/107 family that on the basis of sequence anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…Occluding the middle cerebral artery (MCAo) to the mir-223 knock out mouse increases infarct volume as compared to the wildtype control, and rAAV-mediated transfer of miR-223 reduces infarct volume (Harraz et al, 2012). Similarly, antagomirs to Let7f infused after stroke (Selvamani et al, 2012), mir181a infused before stroke (Moon et al, 2013), and mir103-1 delivered before or after stroke (Vinciguerra et al, 2014) also decreased infarct volume. A recent study also shows that the route of miRNA administration may also affect outcomes, such that intravenous but not intracerebroventricular, mir122 improved stroke outcome in adult rats (Liu da et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…Occluding the middle cerebral artery (MCAo) to the mir-223 knock out mouse increases infarct volume as compared to the wildtype control, and rAAV-mediated transfer of miR-223 reduces infarct volume (Harraz et al, 2012). Similarly, antagomirs to Let7f infused after stroke (Selvamani et al, 2012), mir181a infused before stroke (Moon et al, 2013), and mir103-1 delivered before or after stroke (Vinciguerra et al, 2014) also decreased infarct volume. A recent study also shows that the route of miRNA administration may also affect outcomes, such that intravenous but not intracerebroventricular, mir122 improved stroke outcome in adult rats (Liu da et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…SH-SY5Y cells were incubated in a low serum medium (Guida et al, 2015b) and treated with MeHg 1 μM at 12 and 24 h. For dose-dependent experiments, primary cortical neurons were treated for 24 h with MeHg at 0.1, 0.5, 1, and 3 μM. For SB239063 experiments cells were pre-treated for 2 h with the drug at 10 μM followed with MeHg 1 μM for 24 h. All transfection experiments in SH-SY5Y and cortical neurons were performed 24 h before MeHg treatment (1 μM/24 h) with HiPerFect Transfection Reagent (Quiagen) in accordance with the manufacture's protocol, as previously reported (Vinciguerra et al, 2014). In SH-SY5Y cells and cortical neurons the synthetic small interfering RNA (siRNA) transfections for Sp1 (siSp1), HDAC4 (siHDAC4), and negative control (siCTL) were performed as already reported (Formisano et al, 2015b; Guida et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…AntimiR-103-1 prevented NCX1 protein down regulation induced by the increase in miR 103-1 after brain ischemia, thereby reducing brain damage and neurological deficits. Further they concluded that blocking mir-103-1 by microRNA inhibitors was a reasonable strategy to stop neuro detrimental regulation of NCX occurring during ischemic conditions [40]. …”
Section: Mirna Profile and Function In Animal Brainmentioning
confidence: 99%